The Effect of The Project Based Learning (Pjbl) Model on Students’ Physics Learning Outcomes - Aini, Nurul; Ardhuha, Jannatin; Makhrus, Muh. (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2025)
This study aims to determine the effect of the Project Based Learning (PjBL) model on the physics learning outcomes of eleventh-grade students on the topic of dynamic fluids. This research employed a quasi-experimental method with a pretest–posttest control group design. The population consisted of all eleventh-grade students of SMAN 2 Praya, totaling 170 students across five classes. The sample was selected using cluster random sampling and consisted of class XI-5 as the experimental class, which received the PjBL treatment, and class XI-3 as the control group, which received conventional instruction, with 34 students in each group. Cognitive learning outcomes were assessed using a multiple-choice test consisting of 20 validated and reliable items, while affective and psychomotor outcomes were measured using observation sheets. The hypothesis tested concerned the influence of the PjBL model on students’ physics learning outcomes. Data analysis began with prerequisite tests (normality and homogeneity). Since the data were not homogeneous and not normally distributed, the Mann–Whitney test was used for hypothesis testing. In addition, the N-Gain test was conducted to determine the improvement in learning outcomes. The Mann–Whitney test produced a significance value of <0.001, which is lower than 0.05, indicating that H₀ was rejected and Hₐ was accepted. The N-Gain results showed that the experimental group achieved a high category, while the control group fell into the low category. These findings indicate that the Project Based Learning (PjBL) model has a significant effect on students’ physics learning outcomes.